2018
DOI: 10.1016/j.bbrc.2018.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of EGFR by HOXB5 and its role in breast cancer cell invasion

Abstract: HOX genes are transcription factors that play important roles in body patterning and many cellular processes during embryonic, fetal, and adult development. Given their important function in normal tissues, it is reasonable to assume that abnormal expression of HOX genes in adults could lead to serious diseases such as cancer. Our previous study reported HOXB5 to be significantly up-regulated in breast cancer, and its expression was found to be associated with tumor cell proliferation and invasion. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…4A). HOXB5 is involved in the tumorigenesis and tumor progression of various human cancer types (41)(42)(43); therefore, this gene was selected for validation. The luciferase reporter assay was performed to corroborate the prediction.…”
Section: Mir-944 Directly Targets Hoxb5 Mrna In Tscc Cellsmentioning
confidence: 99%
“…4A). HOXB5 is involved in the tumorigenesis and tumor progression of various human cancer types (41)(42)(43); therefore, this gene was selected for validation. The luciferase reporter assay was performed to corroborate the prediction.…”
Section: Mir-944 Directly Targets Hoxb5 Mrna In Tscc Cellsmentioning
confidence: 99%
“…Lee et al suggested that HOXB5 increased cell proliferation and invasiveness in estrogen receptor-(ER-) positive breast cancer [32]. More interestingly, this research group also found that HOXB5 could upregulate EGFR expression and thereby promote HOXB5driven invasion in ER-positive breast cancer [33]. In this work, we noted that EGFR was involved in cell cycle and proliferation and served as a pivotal hub gene in PPI analysis.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, we found ten genes to be over-expressed in old patients across at least three out of six tumor types. These include COQ3, EYA4, FER1L5, HOXB5, SYS1 and TSNAX and have been associated with a variety of cellular functions including mitochondrial function, tumorigenesis, memory formation and protein trafficking(Behnia et al, 2004; Cannon et al, 2005; Jonassen and Clarke, 2000; Lee et al, 2018). Altogether these findings indicate that primary tumors in younger patients have increased expression of tumor proliferation, progression, and metastasis genes.…”
Section: Resultsmentioning
confidence: 99%